2017
DOI: 10.1021/acs.jctc.7b01000
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Dynamics of Cycloparaphenylenes with TD-DFTB Surface Hopping

Abstract: We implemented a version of the decoherence-corrected fewest switches surface hopping based on linear-response time-dependent density functional tight binding (TD-DFTB), enhanced by transition density analysis. The method has been tested for the gas-phase relaxation dynamics of two cycloparaphenylene molecules, [8]CPP and [10]CPP, explaining some important features of their nonadiabatic dynamics, such as the origin of their long fluorescence lifetimes (related to the slow radiative emission from the S state) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 93 publications
1
79
0
Order By: Relevance
“…Fischer et al 350 322 A reasonable agreement between these methods was found too. Nevertheless, it tends to degrade for delocalized densities.…”
Section: Real-time Methods Ii: Electron-nucleus Couplingmentioning
confidence: 54%
“…Fischer et al 350 322 A reasonable agreement between these methods was found too. Nevertheless, it tends to degrade for delocalized densities.…”
Section: Real-time Methods Ii: Electron-nucleus Couplingmentioning
confidence: 54%
“…In the following, we will use PR NTO , considering that this has already found various applications in the literature 75,[85][86][87] despite its ad hoc nature.…”
Section: General Notationmentioning
confidence: 99%
“…DFTB, as a density functional method, is not initially designed to use wavefunctions to compute properties. Nevertheless, the most common practice is to use the excited state wavefunctions associated with the single excitation configuration interaction (CIS) approximation spanning the TD-DFTB excited states to determine the non-adiabatic couplings presented above [197][198][199][200][201]. This can be achieved through the calculation of the overlap of the CIS electronic wavefunctions between nuclear time steps t and t þ Δt.…”
Section: Global Exploration Of the Energy Landscape And Dynamicsmentioning
confidence: 99%
“…This procedure is described within the framework of TD-DFTB by Humeniuk and Mitrić [200]. Several implementations of FSSH are available within various open-source DFTB codes, such as DFTBaby [200], DFTB+ coupled with the NewtonX or PYXAID packages [201,202] and DeMonNano [203].…”
Section: Global Exploration Of the Energy Landscape And Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation